2022
DOI: 10.4103/indianjpsychiatry.indianjpsychiatry_332_21
|View full text |Cite|
|
Sign up to set email alerts
|

Perceived advantages and disadvantages of telepsychiatry – An online survey of psychiatrists in India

Abstract: Context: Telepsychiatry is being practiced in India for many years but was formalized only in 2020. It has many advantages and disadvantages. Aims: This study aimed to understand the perceived advantages and disadvantages of telepsychiatry practices in India. Settings and Design: An online survey with ethics approval by the Indian Psychiatric Society (IPS) Ethics Review Board. All psychiatrists who are membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…[ 17 18 19 20 ] Even the psychiatrists opined that telepsychiatry will benefit patients in terms of reduced waiting time and travel time. [ 21 ] The availability of telepsychiatry services in or near their communities led to reduced expenses associated with travel and a reduction in missed time at work for caregivers and missed days at school for the ill child and siblings. For many caregivers, an essential benefit of local services is that they can minimize the disruption to their paid employment caused by their relative’s illness.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 18 19 20 ] Even the psychiatrists opined that telepsychiatry will benefit patients in terms of reduced waiting time and travel time. [ 21 ] The availability of telepsychiatry services in or near their communities led to reduced expenses associated with travel and a reduction in missed time at work for caregivers and missed days at school for the ill child and siblings. For many caregivers, an essential benefit of local services is that they can minimize the disruption to their paid employment caused by their relative’s illness.…”
Section: Discussionmentioning
confidence: 99%
“…Psychiatrists acknowledged several advantages of teleconsultation, including time-cost reduction, increased safety, and the ability to see the patient without the mask, which favors a more natural conversation and improves therapeutic alliance ( Thirthalli et al, 2020 ). However, recent surveys revealed that psychiatrists pointed out several drawbacks, including: the fear of potentially dangerous events while dealing with a suicidal or a homicidal patient; the risk of missing out on comorbidities, due to the inability to perform physical and central nervous system examinations; legal/regulatory issues due, for instance, to consultation recording; patients' inability to use conferencing devices; reduced feelings of closeness or connection; and technical problems ( Basavarajappa et al, 2022 ; Guinart et al, 2021 ). Both patients and clinicians expressed concerns about establishing rapport, privacy, safety, and technology limitations, which can contribute to slowing down adoption ( Basavarajappa et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent surveys revealed that psychiatrists pointed out several drawbacks, including: the fear of potentially dangerous events while dealing with a suicidal or a homicidal patient; the risk of missing out on comorbidities, due to the inability to perform physical and central nervous system examinations; legal/regulatory issues due, for instance, to consultation recording; patients' inability to use conferencing devices; reduced feelings of closeness or connection; and technical problems ( Basavarajappa et al, 2022 ; Guinart et al, 2021 ). Both patients and clinicians expressed concerns about establishing rapport, privacy, safety, and technology limitations, which can contribute to slowing down adoption ( Basavarajappa et al, 2022 ). Surveys conducted on patients revealed general satisfaction with the quality of care in telepsychiatry, mainly regarding the perception of health care, but lower satisfaction with the doctor-patient relationship ( Torales et al, 2023 ) and more difficulties establishing a therapeutic alliance, aggravated by the lack of physical proximity and nonverbal clues ( Frittgen and Haltaufderheide, 2022 ).…”
Section: Introductionmentioning
confidence: 99%